Biocontrol mechanisms of Bacillus: Improving the efficiency of green agriculture - Zhang, Nan; Wang, Zhengqi; Shao, Jiahui; Xu, Zhihui; Liu, Yunpeng; Xun, Weibing; Miao, Youzhi; Shen, Qirong; Zhang, Ruifu (Microbial biotechnology, 2023)
Species of the genus Bacillus have been widely used for the biocontrol of plant diseases in the demand for sustainable agricultural development. New mechanisms underlying Bacillus biocontrol activity have been revealed with the development of microbiome and microbe‐plant interaction research. In this review, we first briefly introduce the typical Bacillus biocontrol mechanisms, such as the production of antimicrobial compounds, competition for niches/nutrients, and induction of systemic resistance. Then, we discussed in detail the new mechanisms of pathogen quorum sensing interference and reshaping of the soil microbiota. The “cry for help” mechanism was also introduced, in which plants can release specific signals under pathogen attack to recruit biocontrol Bacillus for root colonization against invasion. Finally, two emerging strategies for enhancing the biocontrol efficacy of Bacillus agents, including the construction of synthetic microbial consortia and the application of rhizosphere‐derived prebiotics, were proposed. In this review, we first briefly introduced the typical Bacillus biocontrol mechanisms. Then, we discussed in detail the new mechanisms of pathogen QS interference and reshaping of the soil microbiota, and the “cry for help” mechanism was also introduced. Finally, two emerging strategies for enhancing the biocontrol efficacy of Bacillus agents, including the construction of synthetic microbial consortia and the application of rhizosphere‐derived prebiotics, were proposed.